Museum of Architecture and Ethnography “Angara Village”: Yesterday, Today, Tomorrow - Selivanenko, Anastasia M.; Селиваненко, А.М. (Сибирский федеральный университет. Siberian Federal University, 2016)
The All-Union scientific-practical conference on the development of the Angara-Yenisei watershed by building several large hydroelectric power plants for subsequent construction of territorial-industrial complexes was held in Irkutsk in 1932. This conception has been implemented since the 50-s of the XX century. Such hyper-industrialization of the region resulted in change of a settlement structure, disappearance of historically rural settlements which are regarded the monuments of wooden architecture, history and culture. The article summarizes the unique experience of rural settlements (the Evenks and the Russian settlers in the XVII – XXI centuries). There is no similar museum in the world, the museum displaying everyday life of the Evenk family. This is viewed as a scientific and practical significance of the museum of architecture and ethnography “Angara village”. The museum also shows the life of the Russian settlers in the XVII – XX centuries. Similar settlements in East Siberia are presented in “Tal’tsy” and “Shushenskoe” outdoor historic museums В 1932 г. в Иркутске прошла Всесоюзная научно-практическая конференция по освоению Ангаро-Енисейского бассейна путем строительства на реках нескольких крупных ГЭС для возведения в последующем территориально-промышленных комплексов. Начиная с 50-х гг. ХХ в. и по настоящее время эта концепция реализовывается в жизнь. В результате гипериндустриализации региона в нем изменилась поселенческая структура, исчезли исторически сложившиеся сельские поселения как памятники деревянного зодчества архитектуры, истории и культуры. В данной статье обобщается уникальный опыт сельских поселений (эвенков и русских поселенцев XVII – ХХI вв.). В мире нет подобного музея, посвященного эвенкам, в котором рассматривались бы жизнь и быт эвенкийской семьи. В этом и состоит научно-практическая значимость архитектурно-этнографического музея «Ангарская деревня». Кроме того, представлен быт русских поселенцев XVII–ХХ вв. В Восточной Сибири аналогичные поселения представлены в музеях-заповедниках «Тальцы» и «Шушенское»